Using behavioral psychotherapy techniques to address HIV patients’ pain, depression, and well-being - Moitra, Ethan (Psychotherapy (Chic), 2019)
For persons with HIV (PWH), aims of psychotherapy can extend beyond HIV-related topics. Issues such as HIV stigmatization and disclosure, and HIV-related self-care including treatment adherence might be ongoing concerns, but, patients often need support to develop skills to manage other problems, whether functional or psychiatric. In the context of an ongoing randomized clinical trial, we delivered an individual, behavioral activation-based intervention to PWH with comorbid chronic pain and depression. Our primary treatment target was to reduce pain-related interference in physical and psychosocial functioning. Throughout the course of the 7-session intervention, clinicians used four core strategies to help patients improve a variety of domains related to their health and well-being: (1) teaching values-based goal setting; (2) developing skills to be an activated and informed patient; (3) focusing on changing behavior despite discomfort; and, (4) facilitating access to care (e.g., flexible scheduling, primarily phone sessions). The application of these strategies to HIV-related and non-HIV-related problems are presented to illustrate how and when clinicians can utilize these strategies. These practical lessons will inform a flexible approach to helping PWH address a myriad of health and functional issues related to their overall well-being.